Challenges and Perspectives in Ensuring Optimal Nutrition for the Elderly - Nazarova Shaxnoza Bayramali qizi; Buranova Gulnoza Boymuratovna (American Journal of Biology and Natural Sciences, 2026)
In the conditions of Uzbekistan, studying the actual nutrition of the elderly and organizing their rational nutrition is one of the important and urgent problems. In order to study the actual nutrition of elderly people, we conducted observation and inspection work among them.